Prognostic Value of the Neutrophil-to-lymphocyte Ratio, Platelet-to- lymphocyte Ratio and Monocyte-to-lymphocyte Ratio in Melanoma Patients: A Cohort Study - Sümeyre Seda Ertekin; Cristina Mangas; Constanza Riquelme-Mc Loughlin; Cristina Carrera; Josep Malvehy; Susana Puig; Sebastian Podlipnik (Medical Journals Sweden, 2024)
The prognostic value of the neutrophil-lymphocyte ratio, platelet-lymphocyte ratio and monocyte-lymphocyte ratio in patients with melanoma has yielded controversial results in the literature. A retrospective single-centre cohort study was conducted from 1998 to 2020, including patients diagnosed with invasive melanoma. A total of 2,721 patients were included in the study. The median follow-up was 8.23 years (IQR 4.41-13.25). The median baseline neutrophil- lymphocyte ratio, platelet-lymphocyte ratio and monocyte-lymphocyte ratio values increased significantly (p < 0.001) with the increasing American Joint Committee on Cancer stage. The optimal cut-off values for neutrophil-lymphocyte ratio, platelet-lymphocyte ratio and monocyte-lymphocyte ratio were determined as 2.1, 184 and 0.2, respectively. In the multivariate analysis, high levels of neutrophil-lymphocyte ratio (≥ 2.1), platelet-lymphocyte ratio (≥ 184) and monocyte-lymphocyte ratio (≥ 0.2) were independently associated with significantly shorter melanoma-specific survival (neutrophil-lymphocyte ratio: HR 1.30, 95% CI 1.06-1.60, p = 0.013; platelet-lymphocyte ratio: HR 1.37, 95% CI 1.06-1.76, p = 0.014; monocyte- lymphocyte ratio: HR 1.29, 95% CI 1.05-1.58, p = 0.015) and overall survival (neutrophil-lymphocyte ratio: HR 1.39, 95% CI 1.19-1.64, p < 0.001; platelet- lymphocyte ratio: HR 1.44, 95% CI 1.19-1.74, p < 0.001; monocyte-lymphocyte ratio: HR 1.42, 95% CI 1.21-1.66, p < 0.001). High levels of neutrophil- lymphocyte ratio and monocyte-lymphocyte ratio were also associated with poor relapse-free survival, while platelet-lymphocyte ratio was not. In conclusion, baseline neutrophil-lymphocyte ratio, platelet-lymphocyte ratio and monocyte-lymphocyte ratio were identified as independent predictors for the prognosis of melanoma.